Роль армии в процессе модернизации Турции в 1960-1990-х годах - Багдасарян, Сурен («Զանգակ - 97»)
At present time ihe whole world feels in either case the influence of modernization process. Still in 1960s there was created the theoiy of modemization, which was connected with the issues of the relationship between the developed countries of the West and the new-independent developing states. Just at that time in histoiy and political science it has putted in operation a term "modernization", which reflects a tend of searching of new ways and models of development by the modern states.
Keywords: История; Турция